2016
DOI: 10.1364/oe.24.015834
|View full text |Cite
|
Sign up to set email alerts
|

Novel robust skylight compass method based on full-sky polarization imaging under harsh conditions

Abstract: A novel method based on Pulse Coupled Neural Network(PCNN) algorithm for the highly accurate and robust compass information calculation from the polarized skylight imaging is proposed,which showed good accuracy and reliability especially under cloudy weather,surrounding shielding and moon light. The degree of polarization (DOP) combined with the angle of polarization (AOP), calculated from the full sky polarization image, were used for the compass information caculation. Due to the high sensitivity to the envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…On all moonlit nights, the highest degree of polarization was measured in a band at approximately 90 deg from the moon (Fig. 2), mimicking that of the sunlit sky (Berry et al, 2004;Horváth et al, 2014), as found for previous studies of the polarization of lunar skylight (Gál et al, 2001;Kyba et al, 2011;Barta et al, 2014;Tang et al, 2016). Although the serial-imaging protocol we employed can lead to the accumulation of motion artefacts, particularly during long exposures, these effects appeared to be limited, for the most part, to a small number of bright stars ( Fig.…”
Section: Polarization Of Lunar Skylightsupporting
confidence: 79%
“…On all moonlit nights, the highest degree of polarization was measured in a band at approximately 90 deg from the moon (Fig. 2), mimicking that of the sunlit sky (Berry et al, 2004;Horváth et al, 2014), as found for previous studies of the polarization of lunar skylight (Gál et al, 2001;Kyba et al, 2011;Barta et al, 2014;Tang et al, 2016). Although the serial-imaging protocol we employed can lead to the accumulation of motion artefacts, particularly during long exposures, these effects appeared to be limited, for the most part, to a small number of bright stars ( Fig.…”
Section: Polarization Of Lunar Skylightsupporting
confidence: 79%
“…On all moonlit nights the highest degree of polarization was measured in a band at approximately 90° from the moon (Fig. 2), mimicking that of the sunlit sky (Berry et al ., 2004; Horváth et al ., 2014), as found for previous studies of the polarization of lunar skylight (Gál et al ., 2001; Kyba et al ., 2011; Barta et al ., 2014; Tang et al ., 2016). Although the serial-imaging protocol we employed can lead to the accumulation of motion artefacts, particularly during long exposures, these effects appeared to be limited, for the most part, to a small number of bright stars (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Pomozi, Horvath, and Wehner (2001) revealed that under clear sky conditions, there are also a certain distribution of sky polarization, which could be utilized by insects. Tang et al (2016) developed a new full-sky polarization imaging sensor, which could get relatively high accuracy of angle of polarization (AOP) under harsh condition. Zhang et al (2015) found a new way to simulate the sky polarization signal obtained by compound eyes of Cataglyphis and validated it through navigation experiments.…”
Section: Introductionmentioning
confidence: 99%